Participatory cowpea development for poverty reduction and sustainable livelihoods in west Africa: case of PRONAF (Projet Niebe pour l'Afrique)- a multipartners, regional, and collaborative project - Adeoti, R.; Coulibaly, O.; Allomasso, R.; Adetonah, S.; Gbaguidi, B.; Fatokun, C. (International Institute of Tropical Agriculture, 2012)
Cowpea has the potential to make a significant contribution to food and nutritional security and poverty reduction in West and Central Africa. Constraints to be addressed include poor access to inputs including seeds, pest control, and product markets for widespread distribution of improved varieties, and integrated pest management technologies to reduce crop losses and improve product quality. The collaborative project between IITA and IFAD (International Fund for Agricultural Development) over a decade has enhanced cowpea production and grain quality through PRONAF, a technologically strong and effective participatory research development and capacity building with NARES and IFAD-funded development projects. PRONAF has made a substantial contribution to developing and disseminating sustainable, improved cowpea innovations in West and Central Africa. Target countries include Benin, Burkina Faso, Cameroon, Ghana, Mali, Niger, and Nigeria. In addition to innovations, capacity building through FFF (Farmer field fora), short courses for training project staff, degree-related training, and exchange of knowledge and information on cowpea value chains have made an important contribution. Several new varieties were released in all PRONAF countries. Good market opportunities have enhanced the willingness of farmers to buy seeds and other inputs. Adoption rates of botanical extracts were 30-40% in Benin and Ghana. Results showed that the transmission of cowpeas' botanical extracts from the current adopters to the potential adopters was influenced by factors including gender. Improved cowpea storage techniques such as the use of solar drying, hermetic drums, and double/triple bagging developed by Bean-Cowpea CRSP have been widely diffused to farmers through NGOs and national extension agents (60% in target countries). Adoption and impact assessment studies of production systems have identified competitive combinations of technologies. In target countries the adoption of cowpea innovations led to an increase in cowpea yield by 20% and incomes by 15%. Increased cowpea production and incomes improve access to food , health, and education. More efforts are needed for capacity building of stakeholders and farmers' empowerment for a wider diffusion of cowpea innovations and substantial impact on welfare target groups.